Morbidity Pattern Among the Rural Household in a Selected Area of Dhamrai Upazila, Dhaka (Anwer Khan Modern Medical College Journal, 2012)
This is a descriptive type of cross sectional study among 477 family heads as respondents. It is aimed to identify morbidity pattern, duration of illness among households' members and also to determine treatment seeking behavior during illness. The socio-demographic characteristics of the respondents are points of investigations. It reveals from the findings that the mean age of the respondents is 35.16 years. They are mostly female (66%) and married (90%). Only 30% respondents are illiterate, 69% respondents are found from nuclear family. The study shows 73% respondents family are suffering from illness during last two months and majority sufferers (19%) and (44%) were less than 5years and more than 31 years old respectively. However, male sufferers were more among 31 years old. Moreover about 43% respondents' family members are suffering for more than 4 weeks and about 29% less than 01 week. On the other hands, Fever, Cough and Pain are found prominent sign/symptoms among 38%, 28% and 29% sufferers respectively. Common cold, Arthritis and Diarrhoea are found as diagnosis among 53.5%, 22.5% & 8.5% respondents' family members respectively. Nevertheless majority 56% are seeking treatment from MBBS doctors. The study findings highlight awareness program among family heads and adult sufferer towards preventing infectious and chronic diseases as well as to undertake modern scientific treatment. Improved surveillance system in the locality may be considered for early detection of cases to treat accordingly to avoid complications. DOI: http://dx.doi.org/10.3329/akmmcj.v3i2.11686 AKMMC J 2012: 3(2): 06-10